EU-INDONESIA CHALLENGES IN RESPONDING TO PALM OIL SUSTAINIBILITY - Akbar Ramadhan; Andi Enrico Maulana; Angela Novahariani; Angelia Deviana Jayanti; Gabriella Elri Tesalonika (Sociae Polites, 2021)
This research article aims to identify the challenges and possible solutions of sustaining palm oil between the European Union and Indonesia by means of diplomacy. Here we have discussed that the European Union with their assumption to restrict if not ban the usage of palm oil and use sunflower oil as an alternative to reduce the extensive deforestation in Indonesia. There are several possible solutions from public diplomacy to lobbying and corporate diplomacy with the purpose to gather and coordinate any type of stakeholders, hence, the lobby is to unify the movement with central leadership.